Assisting Domestic Industries Under International Oligopoly: The Relevance of the Nature of Competition to Optimal Policies - Cheng, Leonard K. (American Economic Review, 1988)
[Optimal trade and industrial policies are derived for a home market that is supplied by a domestic firm and a foreign firm. The optimal policy combination can be quite sensitive to the nature of the duopoly's competition. For example, for some cost and demand structures, the optimal policy under Cournot competition consists of a domestic production tax and a tariff, but that under Bertrand competition consists of a production subsidy and free trade.]